2021
DOI: 10.1017/ice.2021.422
|View full text |Cite
|
Sign up to set email alerts
|

FAST tuberculosis transmission control strategy speeds the start of tuberculosis treatment at a general hospital in Lima, Peru

Abstract: Objective: To evaluate the effect of the FAST (Find cases Actively, Separate safely, Treat effectively) strategy on time to tuberculosis diagnosis and treatment for patients at a general hospital in a tuberculosis-endemic setting. Design: Prospective cohort study with historical controls. Participants: Patients diagnosed with pulmonary tuberculosis during hospitalization at Hospital Nacional Hipolito Unanue in Lima, Peru. Methods: The FAST strategy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…We previously reported that the FAST strategy using Xpert for molecular diagnosis increased the yield of TB diagnosis and decreased time to treatment initiation[ 11 ]. Yet, despite WHO guidance that molecular WHO-recommended rapid TB diagnostic tests (mWRD) such as Xpert should be the initial test for people being evaluated for TB, implementation in Peru and other high-incidence settings has lagged[ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the FAST strategy using Xpert for molecular diagnosis increased the yield of TB diagnosis and decreased time to treatment initiation[ 11 ]. Yet, despite WHO guidance that molecular WHO-recommended rapid TB diagnostic tests (mWRD) such as Xpert should be the initial test for people being evaluated for TB, implementation in Peru and other high-incidence settings has lagged[ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cross-sectional diagnostic accuracy study that was embedded in a larger prospective study evaluating FAST implementation at Hospital Nacional Hipolito Unanue (HNHU), a 700-bed public, tertiary-care referral hospital in Lima, Peru ( https://clinicaltrials.gov/ct2/show/NCT02355223 ). Patients admitted to HNHU from January 18th 2018 to December 31st 2019 were consecutively screened by the FAST implementation team study staff using a standardized questionnaire upon facility admission, as previously described[ 11 ]. This diagnostic accuracy sub-study consisted of two cohorts: triage and screening.…”
Section: Methodsmentioning
confidence: 99%
“…Patients admitted to HNHU from January 18th 2018 to December 31st 2019 were consecutively screened by the FAST implementation team study staff using a standardized questionnaire upon facility admission, as previously described (11). This diagnostic accuracy sub-study consisted of two cohorts: triage and screening.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Most RR/MDR-TB transmission occurs prior to a diagnosis of RR/MDR-TB being made [ 17 ]. Many traditional infection prevention measures, however, are enacted after a person has been diagnosed with RR/MDR-TB.…”
Section: Optimizing Rr/mdr-tb Prevention Through Systematic Post-expo...mentioning
confidence: 99%